Efektivitas Pendekatan Realistic Mathematic Education Pada Operasi Pengurangan untuk Anak Tunagrahita Ringan - Ginting, Sofhia Miranda; Kasiyati, Kasiyati (Jurnal Penelitian Pendidikan Khusus, 2021)
This research background by problems that have been found by researches at SLB Negeri Pembina Tingkat Provinsi Sumatera Utara namely mild mental retardation student in grade V SDLB who had problems subtraction operations. The purpose of this research is to improve the ability of mild mentally retarded students in subtraction using approach of Realistic Mathematic Education (RME). This study using of approach Single Subject Research (SSR) with ABA reseach design and graphic visual analysis techniques. Techniques of data collection in this study used was a test by giving 15 items per session. Overall the results of this study found that approach of Realistic Mathematic Education (RME) can significantly improve student abilities in subtraction.